Experimental research into motor vehicle oscillations in the case of changeable deceleration - Pečeliūnas, Robertas; Prentkovskis, Olegas; Garbinčius, Giedrius; Nagurnas, Saulius; Pukalskas, Saugirdas (Transport, 2005)
In this paper processes of oscillation of flexible mounted and inflexible mounted masses are analysed. The tangential effect of the wheel contact with bearing surface is given, thus enabling more precise calculus of vehicle braking parameters. The methodology of research includes the development of mathematical algorithms and theoretical calculus of the analysed processes as well as the presentation of the influence of various factors on vehicle oscillations during braking. Analytical methods and those in figures have been applied for the research. Experimental investigations were carried out applying the electronic device VZM 100 measuring the acceleration of deceleration adapted for synchronous operation together with vibration processing system VAS‐21. The expert opportunities for modelling of vehicle movement are extended with the help of the created mathematical models used for the examination of road accidents related to vehicle braking. First Published Online: 27 Oct 2010